INDEX PERFORMANCE ANALYSIS KUALITAS LAYANAN DAN MANAJEMEN STRATEGI PENATAAN KAWASAN WISATA SONGGORITI - Dedi Dwilaksana (ROTOR, 2012)
The acceleration of economic growth in the region is supported by the potential of sectoral support the local economy in which one sector is tourism. The development of tourism has an important role for the development of an area, and evenly expand  and employment opportunities, encouraging the development of local, regional and national income increase in order to improve the welfare and prosperity of the community. Stone City is one city where the tourism destination which is Tourism Songgoriti. The potential is very supportive in the growth of the real economy both in terms of products and services. Structuring economic support infrastructure around the holidays can be a priority so that regional economic growth is expected to not only provide opportunities for people with middle and upper economic level but more in favor of increasing the value of the benefit to the surrounding community. To support a more targeted policy measures, especially for the Holidays Songgoriti, it would require an identification of potential research activity in particular economic and business prospects around the area of ​​service quality attributes identified tourism areas Songgoriti desired by consumers (consumer expectations) and how consumer perceptions of attributes -attributes by field survey methods and questionnaires to the respondents who are consumers who have traveled to Songgoiti. Based on data from surveys and questionnaires and supported other secondary data and then do performance Index Analysis (IPA), SWOT Analysis. From the results of the new analyst made recommendations on the business prospects of the development plan Songgoriti tourism area in accordance with the desires of consumers, among others, relating to the restructuring and renovation Songgoriti markets, development of adequate parking facilities, arrangement of PKL to localize them along the roadside as they usually occupy This unique vehicle build date Doloe case of traditional stalls, performances of dance and music studio tadsional, etc.. In order to realize these plans is the management Songgoriti should coordinate intensively with people around the area with government policy support and consistent progressive Rock. Keywords: SWOT Analysis, Index Performance Analysis, intensive coordination